Interaction of myogenic and neurogenic mechanisms that control heart rate. - Brooks, C M (1977)
Interaction of neurogenic and myogenic factors that control heart rate was studied. Sympathetic nerve actions and stretch of the sinoatrial node both have an accelerator effect which appears to be competitive, and additive rather than facilitatory. In contrast with this, the accelerator effects of sinoatrial node stretch were proportionately greater when stretch was applied during a slowing produced by vagus nerve stimulation. The hyperpolarizing effect of vagus nerve stimulation or acetylcholine apparently potentiates the accelerator effects consquent to the depolarizing actions of stretch. The myogenic reaction can be considered as playing a role in maintaining cardiac output and preventing excessive slowing or diastolic distension and a deficient circulation.